2008
DOI: 10.1345/aph.1k284
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine Enhancement of Arousal and Cognition After Traumatic Brain Injury

Abstract: At doses of 200-400 mg/day, amantadine appears to safely improve arousal and cognition in patients with TBI. Additional prospective controlled studies with homogeneous patient populations will better define the role of amantadine for early arousal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 15 publications
2
73
0
2
Order By: Relevance
“…TBI is associated with reduction in the levels of catecholamines such as dopamine. The dopaminergic pathway is thought to regulate cognition and awareness (6,8). Amantadine has been found to improve neurocognitive function and arousal after TBI due to its dopaminergic effect (7,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBI is associated with reduction in the levels of catecholamines such as dopamine. The dopaminergic pathway is thought to regulate cognition and awareness (6,8). Amantadine has been found to improve neurocognitive function and arousal after TBI due to its dopaminergic effect (7,23).…”
Section: Discussionmentioning
confidence: 99%
“…Amantadine, a NMDA receptor antagonist, has been widely studied in patients with traumatic brain injury (TBI), and its efficacy on neurocognitive improvement after TBI has been demonstrated (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Another pharmaceutical mediator which manipulates dopamine in the brain and was remarkably effective on improving aphasia, is amantadine strong agonists of dopamine and norepinephrine receptors as well as a weak antagonist of glutamatergic NMDA receptor. This drug improves cognitive and motivation deficits by increasing the release of dopamine and norepinephrine in neural terminals of mesolimbic and mesocortical pathway (103). Studies report on the recovery of sensory and motor transcortical aphasia by this drug (104).…”
Section: Drugs Acting On Catecholaminergic Systemmentioning
confidence: 99%
“…Many studies have demonstrated that amantadine in dose of 100-400 mg/d may increase the arousal and improve cognitive function when given within 12 wk after the TBI. 37,42 Erythropoietin (EPO). EPO is a secreted glycoprotein with a molecular weight of 30-kD.…”
mentioning
confidence: 99%